Culture and Activism across Borders - Baumgarten, B. (Conceptualizing Culture in Social Movement Research, 2014)
Against the overestimation of processes of cultural homogenization in most studies on globalization, Britta Baumgarten argues for the importance of national borders in transnational activism. There are national differences in certain cultural models and media systems; identities often rely on nationally-bound memories and discourses, and the infrastructure of civil society is mainly shaped by policies at the national level. Nevertheless, Baumgarten argues against container models of national culture and for the investigation of movement subcultures. Movements have developed their own internal cultures over time – related to the national context, but also to other factors. This leads to characteristic cultural differences between movements of different countries that cannot be overcome. They are, however, not only to be understood as obstacles for cooperation but also as fruitful sources for new ideas. To illustrate this, she draws on the current mobilizations in Spain and Portugal.